The first case of lymphogranuloma venereum in a woman in East-Central Europe and its multiple co-infections - Juzlova, Katerina; Rob, Filip; Zakoucka, Hana; Kubatova, Andrea; Secnikova, Zuzana; Krasova, Martina; Bohac, Petr; Hercogova, Jana (Folia microbiologica, 2018)
We are reporting the first case of lymphogranuloma venereum in women in East-Central Europe. A 22-year-old heterosexual woman attended our department of venereology. She complained about a burning sensation in the urethra and vaginal discharge. Many tests were performed, and lymphogranuloma venereum, syphilis, gonorrhea, chlamydial urethritis and cervicitis, genital herpes, genital warts, and hepatitis C were diagnosed. Lymphogranuloma venereum was originally endemic in tropical and subtropical areas, but since 2003, outbreaks of this infection have been reported in North America, Europe, and Australia in men who have sex with men (MSM) community. To date, all cases of lymphogranuloma venereum in the Czech Republic appeared in men, predominantly in HIV-positive MSM. There are not many evidences about lymphogranuloma venereum (LGV) in women in developed countries. This report underlines the need for awareness of lymphogranuloma venereum in women among gynecologists, venereologists, and other physicians not only in Western Europe, but across all European countries.
Keywords: vagina; Chlamydia trachomatis; Urethra; lymphogranuloma venereum; Česká republika; HIV infekce; Adult; mladý dospělý; Czech Republic; uretra; Young Adult; ženské pohlaví; Humans; koinfekce; Vagina; Lymphogranuloma Venereum; dospělí; Coinfection; Female; HIV Infections; lidé